The impact of offshore wind energy on Northern European wholesale electricity prices. (1st July 2023) - Hosius, Emil; Seebaß, Johann V.; Wacker, Benjamin; Schlüter, Jan Chr.
Abstract: Offshore wind energy is experiencing a rising importance for many electricity markets. While the effects of wind energy overall on electricity prices have been thoroughly studied, it remains unknown if offshore wind has a different impact on electricity prices than onshore wind. The aim of this paper is therefore to estimate the effect of offshore wind energy on wholesale electricity prices and how it differs to the impact of onshore wind. For this purpose, we propose three time series models to describe the development of electricity prices in Germany, Western Denmark and Great Britain from 2015–2018. We focus on the impact on the level and volatility of electricity prices using different time series models such as AR-GARCH or ARMA. Following these models, we can identify that onshore and offshore wind power do have a significantly different impact on wholesale electricity prices in the investigated countries. Based on our results, we discuss the implications of our findings for electricity markets and policy makers. Highlights: The results indicate different impacts of off- and onshore wind on wholesale prices Offshore wind tends to reduce price levels and price volatility more than onshore The differential impact of offshore wind is mainly due to a more constant feed-in